The ports of Latakia and Tartous and their role in Syrian foreign trade for the period (1995-2005) (Journal of the College of Basic Education, 2022)
Maritime transport has witnessed remarkable interest as it is the first and most important means in the process of trade exchange, as it secures commercial maritime traffic that exceeds 82% of the volume of international intercontinental trade with other modes of transport.